2021
DOI: 10.1101/2021.08.20.21262382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“The idea is to help people achieve greater success and liberty”: a qualitative study of expanded methadone take-home access in opioid use disorder treatment

Abstract: Background Prior to the COVID-19 pandemic, the United States (US) was already facing an epidemic of opioid overdose deaths. Overdose deaths continued to surge during the pandemic. To limit COVID-19 spread and to avoid disruptions in access to medications for opioid use disorder (MOUD), including buprenorphine and methadone, US federal and state agencies granted unprecedented exemptions to existing MOUD guidelines for Opioid Treatment Programs (OTPs), including loosening criteria for unsupervised take-home dose… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To our knowledge, this study is among a very few to report direct patient experience with policy changes in MOUD access during COVID. A telehealth satisfaction survey was conducted in one Rhode Island provider setting [ 35 ], a survey study of North Carolina patients in three methadone clinics was reported [ 36 ], and a very small, non-peer reviewed study in one San Francisco methadone clinic with 10 providers and 20 patients reported views about methadone take-home dosing [ 37 ]. The North Carolina study found that take-home doses increased from pre-COVID periods to the time of the study (summer 2020) from 56–82% to 78–100%, though notably, the clinic-level percent of patients receiving a week or longer (>6 days) ranged from 11–56%.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is among a very few to report direct patient experience with policy changes in MOUD access during COVID. A telehealth satisfaction survey was conducted in one Rhode Island provider setting [ 35 ], a survey study of North Carolina patients in three methadone clinics was reported [ 36 ], and a very small, non-peer reviewed study in one San Francisco methadone clinic with 10 providers and 20 patients reported views about methadone take-home dosing [ 37 ]. The North Carolina study found that take-home doses increased from pre-COVID periods to the time of the study (summer 2020) from 56–82% to 78–100%, though notably, the clinic-level percent of patients receiving a week or longer (>6 days) ranged from 11–56%.…”
Section: Discussionmentioning
confidence: 99%
“…Since this exemption has been in effect, the number of patients receiving increases in take-home methadone doses has varied between OTPs, however multiple analyses show that a large proportion of patients received an increase in take-home doses after the onset of the pandemic ( Amram, Amiri, Thorn, et al, 2021 ; Figgatt et al, 2021 ; Hoffman et al, 2022 ; Hunter et al, 2021 ; Joseph et al, 2021 ). Evidence from numerous studies has shown that increases in take-home methadone doses following the SAMHSA exemption have not been associated with higher overdose rates, worse treatment outcomes, increased health care utilization, lower adherence to treatment, increased use of illicit opioids or significant diversion of doses among patients on methadone maintenance therapy ( Amram et al, 2021a ; Brothers et al, 2021 ; Figgatt et al, 2021 ; Jones et al, 2022 ; Joseph et al, 2021 ; Knopf, 2020 ; Suen et al, 2021 ). One mixed-methods analysis of patients on MMT in five rural Oregon counties found that each percentage point increase in take-home dosing due to COVID-19 era policy changes was negatively associated with the percent of UDTs positive for opioids other than methadone, as well as the probability of treatment discontinuation ( Hoffman et al, 2022 ).…”
Section: United Statesmentioning
confidence: 99%
“…Even prior to COVID-19, some experts have questioned the utility of regular urinalysis and the lack of take-home dosing, and have posited that financial incentives rather than clinical utility are responsible for driving some of these practices ( Frank et al, 2021 ). Some emerging evidence suggests both clinicians and patients have positive views on these policy changes ( Goldsamt et al, 2021 ; Harris et al, 2021 ; Hunter et al, 2021 ; Madden et al, 2021 ; Suen et al, 2021 ; Treitler et al, 2021 ). A qualitative study of 25 OTP program directors found that most had a generally positive view of the regulatory changes necessitated by the COVID-19 pandemic ( Goldsamt et al, 2021 ).…”
Section: United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The reasons for seeking ED care when using methamphetamine varies with patients requiring anything from medical evaluation for chest pain to sedation and psychiatric evaluation for agitation and psychosis. 12 In some areas, behavioral crises related to methamphetamine use account for half of psychiatric emergency services visits. 13 Additionally, patients who inject drugs, such as methamphetamine, seek ED care for injection-related medical complications.…”
Section: Introductionmentioning
confidence: 99%